Pengaruh Rasio Keuangan terhadap Harga Saham pada PT Bank Rakyat Indonesia (Persero) Tbk Periode 2015–2024 - I Gede Arika; I Komang Widya Purnama Yasa (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study aims to analyze the influence of financial ratios on the stock price of PT Bank Rakyat Indonesia (Persero) Tbk for the period 2015–2024 using quarterly data. Fluctuations in banking stock prices amidst stable profit growth indicate the need for empirical studies on the financial indicators that most influence investor perceptions. This study uses Signaling Theory and Capital Structure Theory as the basis for analysis with independent variables ROA (Return on Assets), CAR (Capital Adequacy Ratio), DER (Debt to Equity Ratio), and EPS (Earnings per Share), and stock price as the dependent variable. Multiple linear regression using the t-test, F-test, and coefficient of determination using SPSS V.27 is the study methodology. According to these results, stock prices are significantly impacted by CAR, significantly impacted by EPS, and not significantly impacted by ROA or DER. Together, the four ratios have a significant impact with a contribution of 67,9% to stock price variations. These findings confirm that CAR is the dominant factor considered by investors in assessing banking stocks.